Emerging free and open source software practices - Sowe, Sulayman K.; Stamelos, Ioannis G., 1959-; Samoladas, Ioannis M.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This book is a collection of empirical research regarding the status of F/OSS projects, presenting a framework and state-of-the-art references on F/OSS projects, reporting on case studies covering a wide range of F/OSS applications and domains. It asserts trends in the evolution of software practices and solutions to the challenges ubiquitous nature free and open source software provides"--Provided by publisher.
Foreword -- Preface -- 1. Volunteers in large libre software projects / Martin Michlmayr, Gregorio Robles, Jesus Gonzalez-Barahona -- 2. Measuring the efficiency of free and open source software projects using data envelopment analysis / Stefan Koch -- 3. Ecology and dynamics of open source communities / Michael Weiss, Gabriella Moroiu -- 4. Perceptions of F/OSS community / Andrew Schofield, Grahame Cooper -- 5. Software development and coordination tools in open source communities / Ruben van Wendel de Joode, Hans de Bruijn, Michel van Eeten -- 6. Evidence-based assurance to support process quality in the F/OSS community / Anas Tawileh, Omer Rana, Wendy Ivins, Stephen McIntosh -- 7. The chase for OSS quality / Benno Luthiger, Carola Jungwirth -- 8. Understanding the development of free e-commerce/e-business software / Walt Scacchi -- 9. The migration of public administrations towards open source desktop software / Kris Ven, Dieter Van Nuffel, Jan Verelst -- 10. Toward a GNU/Linux distribution for corporate environments / Francesco Di Cerbo, Marco Scotto, Alberto Sillitti, Giancarlo Succi, Tullio Vernazza -- 11. Assessing the health of an open source ecosystem / Donald Wynn Jr. -- 12. The rise and fall of an open source project / Graham Morrison -- About.the.contributors - Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 28, 2010).
Keywords: Open source software; Computer software -- Development; Electronic books